Eco-fascism: an oxymoron? Far-right nationalism, history, and the climate emergency - Conversi, Daniele (Frontiers in Human Dynamics, 2024)
Can we conceive of a continuity in the way right-wing nationalisms address environmental issues from the origins of fascism to the currently ongoing global "polycrisis"? This article explores the use of the term "eco-fascism" in connection with the climate crisis and considers the political relationship between ecologism and the contemporary far -right through a historical perspective, seeking to determine persisting patterns in the relationship between the far -right and the environment.Section 1 travels back to the historical origins of this relationship between (nationalism), fascism and the environment, arguing that the conceptions of nature adopted and nourished by fascism had scarcely anything to do with ecology in its contemporary meaning.Section 2 explores The first part of the article considers the most well-known and consolidated studies on the relationship between the far -right and climate change denialism, identifying a broad consensus that unites scholars from various disciplines on the density, intensity, and persistence of this political relationship in the current millennium. millennium.The second part travels back to the historical origins of this relationship, analysing the conceptions of the environment and nature adopted and nourished by fascism since its foundation in post-WWI Italy and its subsequent manifestations in Germany (and elsewhere). This will be placed on a hypothetical continuum with current and contemporary developments.The article concludes by underlining the irreality, falsifiability and internal contradictions of the notion of "eco-fascism" at a time when concludes by underlining the internal contradictions and falsifiability of postmodern notions such as "eco-fascism" at a time when right-wing regimes have taken seized power in many countries through the use of vocabularies and sentiments of in defence of the territory and its resources, but with a substantial refusal to tackle substantial global environmental problems. For this purpose, the more realistic terms "fossil fascism" Malm (Malm 2021)is confirmed, . At the same time, the persisting importance of the overarching notion of ethnonationalism is underlined.The article explores the use of the term eco-fascism in connection with the climate crisis, while omitting those works that bypass, downplay, or fail to mention climate change. [AED1]